The Combination Effects of Physical Exercise and Dzikr for Anxiety Symptoms Improvement in the Elderly Hajj Pilgrim Candidates in Sragen - Arfik Setyanigsih; Probosuseno Probosuseno; Noor Asyiqah Sofia (Faculty of Medicine Universitas Gadjah Mada, 2020)
Background. Anxiety disorders often occur in prospective elderly hajj pilgrims during preparation for departure. Physical exercise and dzikr are recommended as one of the non pharmacological efforts in reducing anxiety disorders.Method. Quasi-experimental one group pretest and post-test with research subjects elderly hajj pilgrim candidates in Sragen in 2019 with symptoms of anxiety that were assessed using the Beck Anxiety Inventory (BAI) score. The intervention was carried out in the form of a combination of forty minutes of physical exercise and thirty minutes of dzikr, 4 times during two weeks and assessed differences in BAI scores before and after the intervention.Aims. To find out the improvement of the BAI score after the combined intervention of physical exercise and remembrance, the Paired t-test was performed if the data distribution was normal and the Wilcoxon test if the data distribution was not normal. Differences were considered significant if p <0.05.Result. There were significant differences in the overall BAI score (p-value <0.001, p <0.05), mild anxiety BAI score (p-value 0.001; p <0.05), systolic blood pressure (p-value 0.002, p<0.05), and pulse frequency (p-value 0.012, p <0.05) before and after the intervention. Obtaining a decrease in systolic blood pressure and a decrease in pulse frequency are parameters for achieving a relaxation response.Conclusions. Significant anxiety symptom improvements were demonstrated as the effect of a combination of physical exercise and dzikr in the elderly hajj pilgrim candidates in Sragen.